Social Class, Gender, and Contemporary Parenting Standards in the United States: Evidence from a National Survey Experiment. - Ishizuka, Patrick (Social Forces, 2019)
Social scientists have documented a substantial increase in both mothers' and fathers' time spent with children since the 1960s in the United States. Yet parenting behaviors remain deeply divided by social class and gender, with important implications for the reproduction of inequality. To understand rising parental investments in children and persistent class and gender differences in parenting, popular accounts and academic studies have pointed to an apparent cultural shift toward norms of time-intensive, child-centered parenting, particularly for mothers and among middle-class parents. However, prior research has produced inconclusive evidence relating to social class, gender, and contemporary parenting norms. Using data from an original vignette survey experiment conducted with a nationally representative sample of more than 3,600 parents, this study examines cultural norms related to parenting elementary school-aged children, considering how both social class and gender shape views about good parenting. Results indicate that parents of different social classes express remarkably similar support for intensive mothering and fathering across a range of situations, whether sons or daughters are involved. These findings suggest that cultural norms of child-centered, time-intensive mothering and fathering are now pervasive, pointing to high contemporary standards for parental investments in children.